Tc interaction with crystalline rock from Äspö (Sweden): Effect of in-situ rock redox capacity. (May 2017) - Huber, Florian Mathias; Totskiy, Yury; Marsac, Rémi; Schild, Dieter; Pidchenko, Ivan; Vitova, Tonya; Kalmykov, Stepan; Geckeis, Horst; Schäfer, Thorsten
Abstract: The interaction of Tc(VII) with crushed crystalline rock (Äspö diorite; 1–2 mm size fraction) from the Äspö Hard Rock Laboratory (HRL) (Sweden) was studied by laboratory batch sorption and desorption experiments under Ar atmosphere using both natural and synthetic groundwater. The Äspö diorite used in the experiments was drilled, transported and handled as far as possible under anoxic conditions to preserve the in-situ rock redox capacity. For comparison, identical experiments using artificially oxidized Äspö diorite have been carried out to examine the effect of in-situ redox capacity on Tc uptake. According to the batch studies, Tc(VII) uptake on the Äspö diorite is strongly dependent on redox capacity. Uptake on un-oxidized rock is approximately 2 times higher compared to oxidized rock samples, most likely due to higher Fe(II) contents of the un-oxidized rock. Tc redox states and speciation both on the mineral surface and in the bulk were studied using X-ray photoelectron spectroscopy (XPS) and Tc K-edge X-ray absorption near edge structure (XANES) spectroscopy. The spectroscopic results verify a Tc(VII) reduction to Tc(IV) at the rock surface. Distribution coefficients (Kd ) and surface normalized distribution coefficients (Ka ) were determined and compared to available literature data. The formation of a Tc colloidal phase was not observed under the geochemical conditions prevailing in the experimental studies. Desorption of Tc is very low under anoxic conditions, but after artificial oxidation Tc mobility is strongly increased. The results of this work clearly highlight the effect of in-situ rock redox capacity on Tc retention. Highlights: Tc sorption/desorption kinetics investigation was performed on both oxidized and un-oxidized Äspö diorite (Sweden). The difference between artificially oxidized and well-preserved natural rock material is shown. Tc colloidal phase formation was not detected under simulated natural conditions. Spectroscopic investigations shown the accumulation of Tc(IV) species on mafic (e.g. mica, magnetite) minerals. Tc sorption parameters on the rock material studied (distribution coefficient, sorption rate) were derived.